Impact assessment of agricultural innovations: a review (2013)
The current conditions of the markets and favorable policies, as well as the progress of science and communications, are promoting further development and diffusion of agricultural innovations, which have effects on different areas of agrarian development. The objective of this paper is to present a review of characteristics of agricultural innovations and their diffusion, adoption and impacts, as well as an update of the types and methods of assessment. Agricultural innovations are not only new or improved products, they are also models and systems, and should have a positive social effect. Innovation areas in developing countries are more concentrated on production and distribution, whereas developed countries concentrate on offering inputs. Investments from the private sector in agricultural innovations are growing faster than those from the public sector. The adoption of innovations is medium-term, and usually less than 100%. The impact of innovations includes intermediate areas, such as institutional, political, scientific and productive areas. The economic efficiency of the investment in innovations is the most often mentioned purpose of impact assessments in the literature. The efficiency analysis (ex-post) and its surplus approach is still the most used method for assessing impact of agricultural innovations. Nevertheless, other goals are becoming more important, such as food security, environmental protection and poverty reduction. Livelihood, comprehensive and multidimensional approaches go beyond the economic approach. Moreover, specific models with advantages of prognosis and improved precision are replacing or complementing the classic socio-economic approach.